BOOK REVIEWS (Journal of Finance, 1954)
Book reviewed in this article: Financial Public Relations: For the Business Corporation . By H erman S. H ettinger The Role of Mergers in the Growth of Large Firms . By J. F red W eston . Personal Finance: Principles and Case Problems . By A rthur H anson and J erome C ohen . Trends in Consumer Finance . By M. R. N eifeld . Speculative and Flight Movements of Capital in Postwar International Finance . By A rthur I. B loomfield Foreign Exchange in the Postwar World . By R aymond F. M ikesell National Incomes and International Trade . By H ans N eisser and F ranco M odigliani . An International Economic System . By J acques J. P olak . Introduction to International Economics . By D elbert A. S nider . Characteristics of Transactions on the Over‐the‐Counter Markets . By M orris H amburg , S tanley S chor , and W illis W inn . Regularization of Business Investment . By U niversities ‐N ational B ureau C ommittee for E conomic R esearch . The Dollar . By R oy F. H arrod . The Economics of Recession and Revival . By K enneth D. R oose . Principles and Practices of Money and Banking . By C harles R. W hittlesey . Effects of Taxation: Investments by Individuals . By J. K eith B utters , L awrence T hompson , and L ynn B ollinger . Taxation in the United States . By R andolph E. P aul . Federal State Local Tax Correlation . A symposium conducted by the Tax Institute. Real Estate Finance . By H enry E. H oagland .